MEMBANGUN BUDAYA AKADEMIK PADA PERGURUAN TINGGI PESANTREN - Muhammad Ridlo Zarkasyi (University of Darussalam Gontor, 2017)
The purpose of this study is to explore the model of of organizational cultureat Pesantren (Islamic boarding) university, the development of academicculture, and how to anticipate the obstacles, and who is responsible and willbe involved in the change and development of the academic culture. Pesantrenuniversity is an institution, which organizes higher education programsand is bound by the Laws regulation, to build an academic culture, which isslightly different from pesantren culture. Building an academic culture meanscreating a new culture within the pesantren envnironment, which focuses onresearch and development activities, which mainly undertakes documentingthe research. Building an academic culture, similar to building an organizationalculture, which can be conducted in the following 6 stages; 1) evaluatingthe organization’s situation and determining strategic objectives and direction;2) analyzing the existing culture and sketching the desired cultural;3) analyzing the gap between what is in and what is desired; 4) developing acultural development plan; 5) implementing the plan; 6) evaluating changesand new efforts to invlove in sustaining cultural change. Steps to build andmaintain an academic culture, carried out in the following combination ofprograms: changes in recruitment and selection procedures; forms socializationand training programs; conducting performance appraisal system; promotingsucessful people in expressing and symbolizing the desired culture;leadership that communicates cultural values in speech, action and materialarrangements; the use of academic symbols, in the form of language, actionand material objects. The actors of change are the Founders and Leaders,who are assisted by the underlying structure with limited proportions. It isnecessary that the appropriate Leadership role to the academic culture, notshifting from the basic values of Pesantren, and open attitude to the development of dynamic academic culture follow the demands of the development of Higher Education.